The mediating effect of job satisfaction on the relationship between HR practices and employee retention among generation Y - Samihah, Suhail (2014)
The objective of the study was to examine the relationship between HR practices and employee retention among generation Y and job satisfaction as a mediating variable. The research done by a questionnaire that distributed to 200 respondents was selected using simple random sampling technique and 160 responded to the questionnaire. Data was analysed by “Statistical Package for Social Science Version 21”. Employee retention among generation Y is an issue which has effected organizations until today. Many organizations have tried to understand the factors that contribute to employee retention among employees. Although many research have been showed the employee retention based on variables such as HR practices (compensation and benefits, training and development and working environment) and job satisfaction, the research conducted may be relevant due to lapse of time. Contemporary studies need to be conducted in order to understand the perception of the new generation of employees particularly among generation Y. New studies need to be conducted in order to understand the new way of thinking among employees especially the new generation and what are the dominant factors that can affected the employee retention among these employees. The study also trying to understand the mediating effect of job satisfaction on the relationship between HR practices and employee retention among generation Y. From that, the study could give more contributions in terms of how job satisfaction could be important and affect the employee retention. Some recommendations have been offered for the organization and practitioners and future research to be more complete and comprehensive.